Relasi Sosial dan Jaringan sebagai Strategi Pengembangan UMKM Kuliner: Peluang dan Tantangan Usaha Kelembut (Kemplang Lembut) - Kesi Anggraini; Citra Mawar Sari; Felix Revaldo; Syarifuddin Syarifuddin; Tyas Fernanda (Forum for Social and Humanities Studies, 2026)
Usaha Mikro, Kecil, dan Menengah (UMKM) are the backbone of Indonesia’s economy, yet they continue to face various challenges such as limited capital, fluctuating raw material prices, and intense market competition. One culinary UMKM rooted in local wisdom is Kelembut (Kemplang Lembut), a specialty from Kayu Agung, South Sumatra, which combines traditional flavors with modern innovation. The main problem addressed in this study is how the Kelembut UMKM can survive and grow amid these challenges. The purpose of this research is to examine the development strategies of Kelembut through social relations and networking, as well as to assess the opportunities and obstacles faced by business actors. The research uses a qualitative case study approach, employing data collection methods such as in-depth interviews, observation, and documentation.. Informants were selected purposively, namely, business actors considered to have relevant information. Data analysis was conducted using thematic methods through reduction, presentation, and conclusion drawing to ensure the validity of findings. The results show that the development strategy of Kelembut UMKM focuses on product innovation, digital marketing, and strengthening local identity. Innovation is carried out through taste standardization, the creation of new variants such as frozen food, and the use of vacuum-sealed packaging that is more hygienic and durable. Digital marketing leverages social media, online marketplaces, and collaboration with UMKM communities to expand distribution networks. Social relations prove to be an essential asset, whether through culinary communities, campus bazaars, or partnerships with resellers and dropshippers. However, limited capital, unstable fish prices, and low digital literacy remain significant barriers. Overall, this study emphasizes that the success of Kelembut UMKM depends not only on internal factors but also on the ability to build social networks and community ties. Strategies based on social relations and continuous innovation are key to enhancing competitiveness while preserving local culinary heritage.